Health preservation activities for students in higher and secondary vocational education: analysis of current research - Safronov, R.V.; Karelina, N.N.; Kasatkin, B.N.; Kokorev, D.A. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to identify methodological approaches in health-promoting activities among students in higher and secondary vocational education. Methods and structure of the study. Dissertation research (abstracts) and articles from peer-reviewed journals were studied, selected according to criteria of relevance, availability of models, conditions and technologies, as well as availability of full text. Theoretical and comparative analysis, structuring and generalisation of data were carried out. Results and conclusions. The dominance of competence-based and integrative approaches is shown; the typical structure of health-saving activities (value-motivational, cognitive, activity-based and reflexive components) is described; key pedagogical conditions and technological solutions are highlighted. The directions requiring further development are identified, including the need to create integrated integrative models and practice-oriented technologies for the formation of health-saving activities of students in vocational education.